4CPS-193 A theoretically based cross-sectional survey on the behaviours and experiences of clinical pharmacists caring for chronic kidney disease patients. (March 2019) - Al Raiisi, F; Al Raiisi, F; Stewart, D; Ashley, C; Fahmy, M; Cunningham, S
Abstract : Background: Chronic kidney disease (CKD) is a comorbid condition with high economic burden. Patients need multiple medications and pharmacists provide care that improves outcomes. A systematic review published in 2012 1 and an update in 2018 2 reported that pharmacists are often poorly integrated within the multidisciplinary CKD team with little description of the practice of pharmacists. Purpose: To describe behaviours and experiences of clinical pharmacists providing care to patients with CKD. Material and methods: This was a cross-sectional online survey using questionnaire items relating to influences on behaviours grounded in the Theoretical Domains Framework (TDF). The questionnaire was reviewed for face/content validity and the subjected to think aloud testing then piloting. Items included; demographics, clinical practice and prescribing practice. The Bristol Online Survey Tool was used with a link emailed to members of a national renal pharmacy group (n=147). The study was approved by a university ethics committee. Results: Responses were received from 36 persons, female (n=25), qualified as pharmacist for >10 years (n=19) and registered active NMPs (n=24). Services provided to inpatients and outpatients are described in the table 1 . While responses to most TDF items relating to clinical practice were positive, the majority (n=24) disagreed that they had sufficient time to practise their role. For prescribing, 16 of the 24 active NMPs were prescribing daily, six weekly and only one ad hoc. They were prescribing in all renal conditions (n=13), dialysis (n=11), transplantation (n=10), anaemia (n=7) and bone mineral disease (n=6). TDF items for prescribing were mostly positive but (n=11) disagreed that they had sufficient time to practise. Conclusion: Results of this survey indicate high levels of complex clinical practice including widespread NMP activity, demonstrating development of practice, including prescribing, since the previous systematic reviews. 1 2 Qualitative research is required to provide further in-depth insights to practice. References and/or acknowledgements: 1. Salgado TM, et al. Pharmacists' interventions in the management of patients with chronic kidney disease: a systematic review. Nephro Dial Transplant 2012;27:276–92. 2. Al Raiisi F, et al. PROSPERO 2017;CRD42017065258. Available from: http://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42017065258 (Accessed 14 November 2018.) No conflict of interest.